MACHINE FOR TESTING SHEARING STRENGTH OF MEDIUM HARD ROCKS - Miroslav Petzel (Rudarsko-geološko-naftni Zbornik, 1993)
Paper describes a shearing machine intended for »softer« rocks with maximal horizontal and vertical force of 400 kN, and surface of samples is between 100 and 200 cm2. The machine can be used for shear tests along the plane of discontinuity of very hard rocks. Average content of CaCO3 in tested samples is 71,39% (the paper is published in Croatian).